Numerical and experimental study of the behavior of a protective structure under impact - D. A. Tarasov (Vestnik MGSU)
Introduction. In connection with the constantly existing threats of deliberate damage to the infrastructure of critical facilities using vehicles, the task of development and research of protective structures aimed at preventing this kind of damage becomes relevant and of practical interest. The application of steel ropes as the main load-bearing elements of such structures is substantiated.Materials and methods. The proposed numerical algorithm was used to determine the minimum permissible cross-sectional area of steel ropes based on the requirements for a protective structure in terms of resistance to impact caused by the collision of a car with a given mass and speed. The developed method is based on mathematical modelling of the conditional optimization problem. The objective function was the function of the longitudinal force arising in the steel ropes. At the same time, requirements were made to comply with the conditions of energy conservation and continuity of deformations, as well as strength limitations. A verification calculation of the designed protective structure was carried out in a commercial software package implemented on the generally recognized finite element method. The methodology of the full-scale experiment is presented. A full-scale experiment was carried out in order to determine the true distribution of deformations over the structural elements of the test object under impact.Results. The results of the experimental study are presented. A comparative analysis of the data obtained in the process of numerical and computer simulation, as well as in the course of a full-scale test, was carried out. A slight discrepancy in the values of the controlled parameters obtained by different methods was found.Conclusions. The proposed numerical algorithm for searching the minimum permissible cross-sectional area of steel ropes, based on the requirement of a given strength, confirmed its reliability, and the adopted design solutions of the developed protective structure proved their validity. The results of the research can be used in the design of such engineering structures designed for the physical protection of critical facilities.